2016
DOI: 10.4236/fns.2016.712108
|View full text |Cite
|
Sign up to set email alerts
|

Informing Food Consumption Choices: Innovations in Measuring and Labelling

Abstract: The need to inform consumers about the health impact of their food choices is ever more pressing in a world where obesity is a growing problem. Concerns over food safety, its origins and its environmental impacts are also growing, as frequently reported in the popular press in many parts of the world. Nutritional and health information on food labels is quite well developed, but the complex nature of the information presented may hinder widespread use of the existing labels. In comparison, there has been littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Of the 10 studies that tested the effects on actual purchases, nine studies significantly favored the intervention, and one study (GHG emissions information in logo form) showed mixed effects across products (Brunner et al, 2018). The studies that favored the intervention condition included three organic claim interventions (two in logo and one in text form) (Aerni et al, 2011; Daunfeldt & Rudholm, 2014; Zanoli et al, 2015), three GHG emissions information interventions (one in text form, one in logo form, and one in combined logo and text form) (Aoki & Akai, 2013; Elofsson et al, 2016; Pelletier et al, 2016), one intervention assessing an environmentally sustainable claim in logo form (Hallstein & Villas-Boas, 2013), and one intervention assessing a water use claim in logo form (Wuepper et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 studies that tested the effects on actual purchases, nine studies significantly favored the intervention, and one study (GHG emissions information in logo form) showed mixed effects across products (Brunner et al, 2018). The studies that favored the intervention condition included three organic claim interventions (two in logo and one in text form) (Aerni et al, 2011; Daunfeldt & Rudholm, 2014; Zanoli et al, 2015), three GHG emissions information interventions (one in text form, one in logo form, and one in combined logo and text form) (Aoki & Akai, 2013; Elofsson et al, 2016; Pelletier et al, 2016), one intervention assessing an environmentally sustainable claim in logo form (Hallstein & Villas-Boas, 2013), and one intervention assessing a water use claim in logo form (Wuepper et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…, 2013; Lee et al. , 2018; Pelletier et al. , 2016); individual aspects, such as sociodemographics, motivations and values (Chen, 2007; Wadolowska et al.…”
Section: Introductionmentioning
confidence: 99%
“…Asp, 1999;Birch, 1999;Capaldi, 1996;Furst et al, 1996;Jaeger et al, 2011;Shepherd, 1989;Vabø and Hansen, 2014;Wansink and Sobal, 2007). The factors influencing final consumers' food decisions include the sensory attributes of foods and the information on the product packaging (Kim et al, 2013;Lee et al, 2018;Pelletier et al, 2016); individual aspects, such as sociodemographics, motivations and values (Chen, 2007;Wadolowska et al, 2008); aspects related to the context and social interaction (Herman et al, 2003;Higgs and Thomas, 2016); and environmental aspects (Furst et al, 1996). Given the complexity and diversity of the aspects influencing consumer food decisions, the work by Shepherd (1989) is of relevance to our research, since it classified the factors affecting food preferences and choice into three main groups: The first group, product-related factors, includes chemical properties of food, sensory qualities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The main limitation of this study is the use of an online simulated contextual policy experiment design rather than a field study. 99 , 100 In a real purchase consumption, it is possible that participants would not make the same choices as in our task, especially given the large influence of habits. 101 , 102 At the same time, questionnaires rely on self-reporting by the public, which may introduce biases associated with data collection.…”
Section: Research Conclusion and Discussionmentioning
confidence: 99%